Oolemmal proteomics – identification of highly abundant heat shock proteins and molecular chaperones in the mature mouse egg and their localization on the plasma membrane - Herr John C; Digilio Laura C; Calvert Meredith E; Coonrod Scott A (Reproductive Biology and Endocrinology, 2003)
Abstract Background The mature mouse egg contains the full complement of maternal proteins required for fertilization, the transition to zygotic transcription, and the beginning stages of embryogenesis. Many of these proteins remain to be characterized, therefore in this study we have identified highly abundant egg proteins using a proteomic approach and found that several of these proteins also appear to localize to the egg surface. Characterization of such molecules will provide important insight into the cellular events of fertilization and early development. Methods In order to identify some of the more abundant egg proteins, whole egg extracts were resolved on coomassie-stained two-dimensional (2D) PAGE gels. Several highly abundant protein spots were cored and microsequenced by tandem mass spectrometry (TMS), and determined to be molecular chaperone proteins. Concurrent experiments were performed to identify oolemmal proteins using 2D avidin blotting. Proteins spots that appeared to be surface labeled by biotinylation were correlated with the initial coomassie-stained reference gel. Surprisingly, some of the surface labelled proteins corresponded to those abundant chaperone proteins previously identified. To confirm whether these molecules are accumulating at the oolemmal surface in eggs, we performed immunofluoresence on live, zona-free eggs using antibodies to HSP70, HSP90, GRP94, GRP78, calreticulin and calnexin. Results The putative surface-labeled proteins identified by biotinylation included the molecular chaperones HSP70 (MW 70 KDa, pI 5.5), HSP90a (MW 85 KDa, pI 4.9), GRP94 (MW 92 KDa, pI 4.7), GRP78 (MW 72 KDa, pI 5.0), Oxygen regulated protein 150 (ORP150; MW 111 KDa, pI 5.1), Calreticulin (MW 48 KDa, pI 4.3), Calnexin (MW 65 KDa, pI 4.5), and Protein disulfide isomerase (PDI; MW 57 KDa, pI 4.8). Immunofluoresence results showed that antibodies to HSP90, GRP94, GRP78 and calreticulin were reactive with oolemmal proteins. We were unable to confirm surface localization of HSP70 or calnexin by this method. Conclusions We report here the identification of nine highly abundant molecular chaperones in the mouse egg proteome. In addition, we present preliminary data suggesting that these molecules localize to the oolemma of the mature mouse egg.